The Concept of Spirituality in the Health Sector: Contributions from the Study of Religion - Stern, Fábio L. (International journal of Latin American religions, 2022)
This article aims to address the possible problems of the polysemy of the term "spirituality" as it has been used in the health area. To this end, we divide this study into three parts. In the first part, we present the definitions of "spirituality" in the human sciences, its historical relationship with Christian theology, and its recent re-signification by the New Age movement. Next, we demonstrate how most of the productions in the health area adopt a reified and essentialized conception of spirituality. In the third section, we discuss the main weaknesses identified in the study. The term spirituality is being used in the medical sciences to allow religion to enter its spaces, including public policies, although secularized. We draw a parallel with the phenomenology of religion to demonstrate the consequences of a misconceived category in the long run. Finally, we identified an overvaluation of the psychological dimension of spirituality to the detriment of the moral and ritual dimensions.